(untitled) (International Research in Economics and Finance, 2022)
At present, the market economy system is constantly reforming and upgrading, and the market competition is becoming more and more intense, which also brings new challenges and opportunities for various industries. The application of supply chain management in logistics network can effectively create revenue for enterprises, optimize the sharing and joint utilization of their information resources. It is a scientific and advanced management mode in today’s environment. So how to effectively maximize the benefits of supply chain management logistics network and enhance the core competitiveness of enterprises, the following will be the background of supply chain management, logistics network economics of win-win strategy, risk and credit and other aspects of the specific analysis, the use of economic principles to explore the concept of enterprise logistics management, technology backwardness and other issues and put forward relevant strategies for reference.